Building a multilingual ontology for education domain using monto method - Merlin Florrence (Computer Science and Information Technologies, 2020)
Ontologies are emerging technology in building knowledge based information retrieval systems. It is used to conceptualize the information in human understandable manner. Knowledge based information retrieval are widely used in the domain like education, artificial intelligence, healthcare and so on. It is important to provide multilingual information of those domains to facilitate multilanguage users. In this paper, we propose a multilingual ontology (MOnto) methodology to develop multilingual ontology applications for education domain. New algorithms are proposed for merging and mapping multilingual ontologies.